Gambaran pengetahuan, sikap dan perilaku tentang manajemen diet pada pasien hipertensi di Garut, Indonesia - Via Komalasari; Iwan Shalahuddin; Hasniatisari Harun (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Hypertension knowledge, attitudes, and behavior related to diet management among patient with hypertension in Garut-IndonesiaBackground: Hypertension is a non-communicable disease in which cases are still many in Indonesia. The knowledge, attitude and patient behavior with proper diet management would like to recover. Knowledge is something that can underlie or encourage someone to take action or behavior. The recommended hypertension diet for people with hypertension is the consumption of food that is low in salt, low in fat, increase fibre, increase potassium intake, do not consume cigarette, coffee and alcohol, increase consumption of vegetable and fruit.Purpose: To determine description of Hypertension knowledge, attitudes, and behavior related to diet management among patient with hypertension in Garut-IndonesiaMethod: A quantitative approach with the population were patient with hypertension in Guntur Health Center, the samples were of 159 respondent using accidental sampling techniques. The instrument used as a questionnaire which includes knowledge, attitude and behaviour. Data analysis used univariate analysis.Results: Showed that most respondents had a good level of knowledge of 152 (95,6%) respondent,159 people (100%) had a supportive attitude, and of 159 (100%) respondent had a positive behavior. Reported that there were some behaviours need to change or preserve as local wisdom such as reducing the consumption of full cream milk, biscuit and egg yolk and maintaining consumption of fruit, vegetable and food that contain low fat.Conclusion: Base on the result expected to use as a reference and learning both in the provision of health education or other nursing care for the knowledge, attitude and behaviour of hypertension sufferers about dietary.Keywords: Hypertension; Knowledge; Attitudes; Behavior; Diet management; Patient.Pendahuluan: Diet hipertensi merupakan salah satu penatalaksanaan hipertensi yang mudah untuk diubah. Diet hipertensi bisa meningkatkan status kesehatan seseorang, status kesehatan seseorang bisa dipengaruhi oleh perilaku. Faktor yang yang erat kaitanya dengan perilaku adalah pengetahuan dan sikap. Pengetahuan yang baik dan sikap yang mendukung akan membantu terlaksananya penatalaksanaan hipertensi dengan benar.Tujuan: Untuk mengetahui gambaran pengetahuan, sikap dan perilaku penderita hipertensi tentang manajemen diet. Metode: Penelitian deskriptif kuantitatif, populasinya semua pasien yang menderita hipertensi di wilayah Garut dengan jumlah sampelnya sebanyak 159 responden dengan teknik pengambilan sampel accidental sampling. Instrumen yang digunakan dalam bentuk kuesioner, yang meliputi: pengetahuan, sikap dan perilaku. Analisis data menggunakan analisis univariatHasil: Menunjukan bahwa sebagian besar responden memiliki tingkat pengetahuan baik yaitu 152 orang (95,6%), sebanyak 159 (100%) responden memiliki sikap yang mendukung dan 159 (100%) responden memiliki perilaku yang positif.Simpulan: Ada beberapa perilaku yang harus ditingkatkan seperti mengurangi konsumsi susu full cream, biskuit dan kuning telur serta mempertahankan perilaku yang sudah baik seperti konsumsi buah, sayur dan makanan yang mengandung rendah lemak.